Bentonite in two-component grout applications. (June 2022) - Todaro, Carmine; Saltarin, Simone; Cardu, Marilena
Abstract: Two-component grout is a cement-based material, currently the most used technology for backfilling in tunnelling applications. Despite its intensive, knowledge on this material is quite limited, especially as concern the role of ingredients and their effect on the properties of fresh mortar and hardened grout. In this work, an accurate and innovative test campaign focused on the role of the bentonite was performed. Three different bentonites were used. The activation of the bentonite and its effect on both mortar stability and grout strength was investigated with the purpose to recognise the bentonite parameters useful to select, at the design stage, the best bentonite according to the designers' requirements. Swell index and Atterberg's liquid limit were recognised as useful parameters for predicting results in terms of suitable bleeding and surface compression strength. Highlights: Activation time of bentonite plays an active role in the bleeding reduction. Bentonite is involved in the strength of the grout at short curing time. Swell index and Atterberg's liquid limit can be used for the bentonite selection.